Ressonância paramagnética eletrônica de compostos orgânicos halogenados de cu (ii): CuTz2X2 E Cu(MA)2X4 (Tz = C3H3NS, MA = CH3NH3+ E X = Cl-, Br-) - Luciano Gabriel Silva (2018)
Organic compounds with magnetic transition metals have been intensively studied for applications in spintronics because they ally the flexibility of the organic group with the magnetism of the metal. Most organic elements of these compounds usually have small spin-orbit interactions and also several carbon nuclei whose abundance of isotopes with non-zero nuclear spins is very small. Both facts contribute to polarized spin chains possessing long lifetimes that are crucial for spintronics applications. Most of them are paramagnetic at high temperatures and ferro- or antiferromagnetic with 1D or 2D ordering below a critical temperature (Tc). In this work, we have studied four Cu2+ halogenated polycrystalline organic compounds that exhibit several of the above properties. These compounds, depending on their structure, are divided into two groups: di-halides and thiazole groups: Cu(C3H3NS)2Cl2 and Cu(C3H3NS)2Br2; tetra-halides and methyl-ammonium groups: Cu(CH3NH3)2Cl4 and Cu(CH3NH3)2Br4. After a preliminary analysis by X-ray diffraction, these compounds were systematically investigated by Electronic Paramagnetic Resonance (EPR). At room temperature, the powder spectra were measured, analyzed and quantified; and this confirmed that the all paramagnetic centers are Cu2+. EPR measurements were performed at different temperatures, between room temperature and approximately 4.2 K. We then refined the spin Hamiltonian parameters obtaining several informations. Undoubtedly, the most relevant one concerns about the Cu(C3H3NS)2Cl2 compound. For this compound, we show that there is a reduction of the coordination symmetry structure around the Cu2+, dominated by the dynamic Jahn-Teller effect, at high temperatures (tetragonal D4h), to one governed by the static Jahn-Teller effect, at temperatures lower than 50 K (rhombic D2h). Furthermore, in all samples, we have verified that hyperfine and superhyperfine interactions are not observable because of the presence of exchange interaction between Cu2+ due to the proximity of them. Finally we discuss the origin and possible nature of the magnetic ordering below Tc after monitoring the changes of the line width and the g tensor.